Pelatihan Pembuatan Penyedap Rasa Non-MSG Berbahan Dasar Jamur Tiram Putih di Kelurahan Karang Taruna, Kecamatan Pelaihari, Kabupaten Tanah Laut, Kalimantan Selatan: Training on Making non-MSG Flavoring Made from White Oyster Mushrooms in Karang Taruna Village, Pelaihari District, Tanah Laut Regency, South Kalimantan - Rizali, Akhmad; Sari, Noorkomala; Jannah, Nurika Ahlul; Azzahra, Sorraya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Karang Taruna Village has a group of oyster mushroom farmers where, under certain conditions, the productivity of oyster mushrooms that are too high can cause difficulties. The rainy season with high humidity will increase oyster mushroom growth, so harvests often occur. In addition, if the baglog used is new or when it enters the early harvest stage, the yield will usually peak. Judging from the problems of related partners, which can be seen in the condition of the oyster mushrooms' durability, which is susceptible to damage, it is necessary to diversify the processing of oyster mushrooms. An example of processed oyster mushroom products is non-MSG flavoring, which can be seen in the condition of the people of South Kalimantan, who have switched to using non-MSG seasoning because they are aware of healthy living but still want their food to have added flavoring. The fear that still haunts the public with the COVID-19 outbreak has made people now look for many products, both food and beverages, that can increase immunity as well as products that can prevent various kinds of diseases that will attack and the level of people's dependence on flavoring products. In this condition, the products offered to related partners are expected to become superior products in great demand and promise a large market segment so that, in the future, the family economic sector can improve.